1958
DOI: 10.1085/jgp.42.2.289
|View full text |Cite
|
Sign up to set email alerts
|

Some Observations on Cardiac Automatism in Certain Animals

Abstract: Certain aspects of the acetylcholine hypothesis of cardiac automatidty have been tested in dtro with spontaneously beating cardiac tissue from rabbits, rats, dams, and hagfish. The beat of atria from rabbits and rats may be depressed or excited by acetylcholine, depending upon the state of the tissue. Proguanil and cocaine inhibition of the beat in the rat may be antagonized by acetylcholine so that reversal of the depression occurs. The action of acetylcholine on the hearts of dams was found to be strictly in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1971
1971
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…In case of the heart rate, there is a different approach in our study compared to Bullfrog ( Lithobates catesbeianus ), 57 where changes in resting heart rate after metamorphosis were reported. While the study of measured the heart rate in vivo, 57 we used ex vivo approach, where the heart rates ex vivo reflects automaticity of the unregulated pacemaker 58,59 . In the amphibians, already at the larval stage, the resting heart rate is affected by vegetative nervous system 57,60 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In case of the heart rate, there is a different approach in our study compared to Bullfrog ( Lithobates catesbeianus ), 57 where changes in resting heart rate after metamorphosis were reported. While the study of measured the heart rate in vivo, 57 we used ex vivo approach, where the heart rates ex vivo reflects automaticity of the unregulated pacemaker 58,59 . In the amphibians, already at the larval stage, the resting heart rate is affected by vegetative nervous system 57,60 …”
Section: Discussionmentioning
confidence: 99%
“…While the study of measured the heart rate in vivo, 57 we used ex vivo approach, where the heart rates ex vivo reflects automaticity of the unregulated pacemaker. 58,59 In the amphibians, already at the larval stage, the resting heart rate is affected by vegetative nervous system. 57,60 Morphological changes showed differences in trabeculation between the P and the M axolotl groups, which are more likely connected to terrestrial life-style.…”
Section: Metamorphic Changes In the Axolotl Heartmentioning
confidence: 99%
“…The preparation used here did not include the sinus venosus, which acts as the pacemaker in vivo (Davie et al 1987). However, bearing in mind the relative constancy of heart rates at rest and when swimming (Forster et al 1987), it is likely that the marked changes in heart rates of isolated hagfish hearts reported earlier (Jensen 1958) represent an artefact of the recording conditions and perhaps inadequate perfusion volumes. For example, Chapman et al (1963) reported an A-V block in experiments on the isolated heart of E. stouti, which was not seen in these experiments.…”
Section: Discussionmentioning
confidence: 99%